A Needs Analysis on Developing Culture-Based Supplementary Reading Materials about Pontianak Malay Kingdom - Dudy Effendy; Uray Salam; Iwan Supardi (Departement of Mathematics Education, 2020)
The disparity in cultural representation within English textbooks in Kalimantan Barat schools has prompted concerns among educators, especially in junior high schools. The dominance of international books, primarily authored by Western writers, neglects the unique culture of Kalimantan Barat. This study addresses the need for a contextual-cultural learning model in English education by focusing on the Malay culture of Pontianak, given its prominence in the region. The research includes a thorough needs analysis to understand students' English competence, expectations, and perceptions of course books. Through questionnaire conducted at SMP Gembala Baik Bilingual Class, the study explores students' interests, preferences, and the role of local culture in English learning. Findings reveal a positive perception of the teaching and learning process, with an emphasis on the importance of reading in English. Students express a keen interest in incorporating local culture into reading materials and a unanimous acknowledgment of the need for additional resources. The study highlights opportunities for enhancing engagement through diverse reading materials, culturally relevant content, and flexible technology integration.In conclusion, addressing cultural disparities in English education necessitates an inclusive approach. This research provides valuable insights for educators to tailor instruction, integrate local culture, and use technology effectively, ultimately creating a more engaging and relevant learning experience for students in Kalimantan Barat.